Comparative Efficacy of Aliskiren/Valsartan vs Valsartan in Nocturnal Dipper and Nondipper Hypertensive Patients: A Pooled Analysis - Giles, Thomas D. (J Clin Hypertens (Greenwich), 2012)
J Clin Hypertens (Greenwich). 2012; 14:299–306. ©2012 Wiley Periodicals, Inc. This pooled analysis of ambulatory blood pressure (BP) monitoring data from two 8‐week randomized controlled trials compared the antihypertensive efficacy and safety of combination aliskiren/valsartan vs valsartan alone in hypertensive patients (nocturnal dippers or nondippers). At study end, patients were taking aliskiren/valsartan 300/320 mg or valsartan 320 mg. In dippers (n=138) and nondippers (n=132), aliskiren/valsartan provided significantly (P<.05) greater reductions from baseline to week 8 than valsartan in 24‐hour, daytime, and last‐4‐hour mean ambulatory systolic BP (maSBP). Treatment differences were more pronounced in nondippers. Nighttime maSBP reductions with aliskiren/valsartan were significantly greater vs valsartan in nondippers (−17.0 mm Hg vs −8.9 mm Hg; P<.05) but not dippers (−7.6 mm Hg vs −4.5 mm Hg; P=.16). In all time periods, combination therapy was generally associated with BP reductions that were greater in nondippers than dippers. Conversion from nondipper to dipper status was 32% vs 22% for aliskiren/valsartan vs valsartan (P=.48). Both treatments were similarly well tolerated. Although the addition of aliskiren to valsartan did not significantly alter dipper status, our data suggest an increased contribution of the renin‐angiotensin‐aldosterone system to the nondipper status of hypertensive patients.